2017
DOI: 10.1148/radiol.2017161872
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Small Focal Renal Lesions: Diagnostic Accuracy with Single-Phase Contrast-enhanced Dual-Energy CT with Material Attenuation Analysis Compared with Conventional Attenuation Measurements

Abstract: Purpose To determine whether single-phase contrast material-enhanced dual-energy material attenuation analysis improves the characterization of small (1-4 cm) renal lesions compared with conventional attenuation measurements by using histopathologic analysis and follow-up imaging as the clinical reference standards. Materials and Methods In this retrospective, HIPAA-compliant, institutional review board-approved study, 136 consecutive patients (95 men and 41 women; mean age, 54 years) with 144 renal lesions (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 23 publications
1
28
2
2
Order By: Relevance
“…We demonstrated a size-specific dose reduction on average of 51%, and this reduction was higher for the dual-source DE CT (65% vs 44%). This is in accordance with previous renal lesion imaging studies (6,11,12,17,(30)(31)(32). However, approaches maintaining diagnostic performance should always precede dose reduction, as this may only lead to inconclusive examinations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We demonstrated a size-specific dose reduction on average of 51%, and this reduction was higher for the dual-source DE CT (65% vs 44%). This is in accordance with previous renal lesion imaging studies (6,11,12,17,(30)(31)(32). However, approaches maintaining diagnostic performance should always precede dose reduction, as this may only lead to inconclusive examinations.…”
Section: Discussionsupporting
confidence: 88%
“…Our final single-center retrospective study population was composed of 293 patients. The study patients are part of a large retrospective DE CT database, of which 85 patients have been reported in previously published studies (12)(13)(14) from our institution. In patients with multiple renal lesions (n = 86), up to five of the smallest lesions (1.0 cm) in each patient were included because small lesions represent the biggest challenge for characterization in clinical practice.…”
mentioning
confidence: 99%
“…We did not assess the diagnostic performance of iodine concentration for renal lesion characterization. There is accumulating evidence to suggest that direct quantification of iodine concentrations has several important benefits, including improved sensitivity in the detection of lesion vascularity (24,30), decreased reader interpretation times (24,31,32), and higher quantitative value due to the lack of variability from differences in ROI positioning during conventional measurements of lesion enhancement (33). We excluded renal lesions smaller than 10 mm in size; these results may not extend to assessment of subcentimeter renal lesions due to increased susceptibility of small lesions to pseudoenhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that dual-energy CT can improve the differentiation between nonenhancing cysts and low-level-enhancing tumors [8][9][10][11]. Dual-energy CT with reconstruction of virtual monochromatic images has been shown to decrease or overcome renal cyst pseudoenhancement [12].…”
Section: Special Imaging Considerationsmentioning
confidence: 99%